Frontispiece: Tracking the Process of a Solvothermal Domino Reaction Leading to a Stable Triheteroarylmethyl Radical: A Combined Crystallographic and Mass‐Spectrometric Study. Issue 12 (13th March 2019) - Liu, Bin; Yu, Fei; Tu, Min; Zhu, Zhong‐Hong; Zhang, Yuexing; Ouyang, Zhong‐Wen; Wang, Zhenxing; Zeng, Ming‐Hua
Abstract : Domino Reactions . In their Communication on page 3748 ff., M.‐H. Zeng et al. describe the synthesis of a free carbon radical through the domino reaction of a primary amine with FeCl3 ⋅6 H2 O in methanol under solvothermal conditions.